A Large-Scale Magnetic Field Generation System for Pesticide-Free Agriculture Based on Cascaded Inductive Coupling - Liu, Zhan; Xu, Ziyang; Wang, Yifan; Liu, Ming (IEEE journal of emerging and selected topics in industrial electronics (Print), 2025)
High frequency magnetic field has been confirmed to have significant influence on insects and plants, which provides the possibility for future pesticide-free agriculture applications. However, existing magnetic field generation (MFG) devices are bulky, inefficient, and heavily placement-restricted, which are not suitable for agricultural environments. In this article, one novel cascaded inductive coupling based MFG system is proposed, which can generate large-scale magnetic field between cascaded coupled coils with very low-power consumption and space occupation. Moreover, constant currents can be achieved in multiple transmitting modules to ensure the identical magnetic fields by using the proposed approach when considering the features of MFG application, i.e., the no-load terminal and all power consumed on the coils and other parasitics. To validate the proposed MFG system and its design, the MHz prototyping systems with 8 coils, 12 coils, and 16 coils, are fabricated for testing and compared to the conventional design for inductive power transfer (IPT) systems. The experimental results demonstrate the effectiveness of the proposed approach. In the proposed MFG system with 16 coils (8 modules), the transmitter (TX) currents of all the modules can keep the same while the TX current variation is 40% higher in the conventional design for IPT system.